Assessing travel satisfaction in public transport: A configurational approach. (April 2021) - Sukhov, Alexandre; Lättman, Katrin; Olsson, Lars E.; Friman, Margareta; Fujii, Satoshi
Highlights: A configurational approach unveiled the complexity of travel satisfaction. Travel satisfaction is achieved by different configurations of quality attributes. Safety has an inherent part in experiencing high travel satisfaction. Context play a key role in how users of public transport experience service quality. Abstract: Previous findings have established that satisfaction with public transport service quality attributes (reliability/functionality, information, courtesy/simplicity, comfort, safety) relate to overall travel satisfaction. Recent studies propose that the importance of these attributes for travel satisfaction varies in different contexts and call for new approaches for enhancing the understanding of these relationships. We address this call by using a configurational perspective and applying fuzzy set Qualitative Comparative Analysis (fsQCA), to explore how satisfaction with service quality attributes relate to high travel satisfaction. By analyzing user survey data before and after an intervention in public transport services in a Swedish city, we: 1) find that high travel satisfaction occurs in the interaction between service quality attributes; 2) identify different configurations of satisfaction with service quality attributes leading to high travel satisfaction; and 3) show how context alters overall travel satisfaction. We conclude that using a configurational approach is useful for understanding the complexity of travel satisfaction.